Recording Insurance Transactions in the Balance of Payments - Harper, Peter (IMF Working Papers; Working Paper, 1995)
Insurance enterprises provide services, called insurance services, to policyholders. The values of such services are seldom, if ever, directly apparent; rather these values are implicitly entwined within the payment of premiums. This paper discusses the treatment of insurance services, and related transactions, in the balance of payments. A simple measure, based on a number of assumptions, of nonlife insurance services is considered. The assumptions underlying this measure are then relaxed. The treatment of life insurance, which has many of the characteristics of nonlife insurance, is then addressed. The paper concludes with a discussion on the practical aspects of measuring insurance transactions in the balance of payments.